2004
DOI: 10.1158/0008-5472.can-3299-2
|View full text |Cite
|
Sign up to set email alerts
|

Lineage Infidelity of MDA-MB-435 Cells

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
48
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 150 publications
(51 citation statements)
references
References 32 publications
3
48
0
Order By: Relevance
“…The origin of MDA-MB-435 cells has recently been called into question (54,55). However, a latest literature indicated that MDA-MB-435 cells are in fact breast cancer cells and not of melanoma origin (56).…”
Section: Discussionmentioning
confidence: 99%
“…The origin of MDA-MB-435 cells has recently been called into question (54,55). However, a latest literature indicated that MDA-MB-435 cells are in fact breast cancer cells and not of melanoma origin (56).…”
Section: Discussionmentioning
confidence: 99%
“…Extensive work from the M. D. Anderson Cancer Center shows that these cells express breast-specific (nonmelanocyte) markers and can be induced to secrete milk proteins and lipids (56). Furthermore, these cells preferentially grow when implanted into mammary fat pads compared with subcutaneous injection (57), similar to other breast cancers but unlike melanoma cell lines.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, Daoy cells also express EagII naturally, which provided a good internal control. The third cell line, MDA-MB435S, is derived from a pleural effusion of a mammary carcinoma, although it seems more related to melanomas rather than carcinomas as revealed by gene array experiments (36,37) and expresses a lower amount of EagI (1000 -5000 copies/l). MDA-MB435S cells also express small amounts of EagII.…”
Section: Discussionmentioning
confidence: 99%